MICRO-STORIES OF GERMAN SPEAKING INHABITANTS OF THE POZNAŃ PROVINCE AND GEOPOLITICS - Nowikiewicz, Elżbieta (Porównania, 2013)
The study of the history of the lands which were within the old borders of the Poznań Province (1815–1918) was, during the partitions, a tool which was used to define, create and manipulate self-defining of German speaking newcomers/migrants. A lot of attention was paid, for obvious reasons, to relations of these lands with the Prussian and German past, which was to legitimize and promote the German presence in this area. The local identity, built and spread in this way was expressed by an instrumental use of the past of the Poznań Province. It is worth answering a question about the role of politics in re-defining a historical view of the Poznan Province and the ways in which the ‘imposed’ reinterpretations of the region’s history and current actions of the authority were perceived by ordinary citizens. It is difficult and still being researched. However, certain regularities can be noticed in the light of autobiographical narration. Micro-stories can help to answer the question whether the authors in their personal reflections identified themselves with the political line of the rulers, how they experienced and remembered the actions of the state, how they remembered and wrote about them, in other words, how actual, experienced and remembered histories coexist.